Visualization and bibliometric analysis of 3D printing in cartilage regeneration - Yang, Zhen; Li, Jianwei; Deng, Haoyuan; Li, Hao; Zhao, Tianyuan; Gao, Tianze; Xing, Dan; Lin, Jianhao (Frontiers in Bioengineering and Biotechnology, 2023)
The self-repair ability of cartilage defects is limited, and 3D printing technology provides hope for the repair and regeneration of cartilage defects. Although 3D printing technology and cartilage repair and regeneration have been studied for decades, there are still few articles specifically describing the relationship between 3D printing and cartilage defect repair and regeneration, and a bibliometric analysis has not been completed. To supplement, sort out and summarize the content in related fields, we analyzed the research status of 3D printing technology and cartilage repair and regeneration from 2002 to 2022. According to the set search strategy, the Web of Science Core Collection was used as the data source, and the literature search was completed on December 6, 2022. CiteSpace V and VOSviewer were used as bibliometric tools to complete the analysis of the research focus and direction of the published literature. Based on the analysis results, we focus on the occurrence and development of this field of combined medical and engineering research. Moreover, the current advantages and limitations of this field as well as future development prospects are discussed in depth.